The effects of slow-stroke back massage on anxiety and sleep problems in elderly stroke patients - Syarifah Lubbna; Awis Hamid Dani; Septi Warni Asih (Malahayati International Journal of Nursing and Health Science, 2023)
Background: The increasing population of the elderly may cause a large burden of health problems, such as poor sleep quality and anxiety. It was reported that as many as 20 percent – 50 percent of the elderly population in Indonesia experienced sleep problems, and 35 percent of the elderly who had anxiety also had the same problems. Slow Stroke Back Massage (SSBM) may be given as a non-pharmacological to increase sleep quality.Purpose: To analyze the effect of SSBM on sleep quality and anxiety in the elderly at the Tresna Wreda As-Salaam Social Institution, Cirebon City.Method: The pre-experimental design with one group pretest and posttest design. The 15 elderly was the sample, as a total sampling technique was used.  The Pittsburgh Sleep Quality Index (PSQI) and Geriatric Anxiety Scale (GAS) questionnaires were used as instruments for measuring sleep quality and anxiety levels. The sleep quality was analyzed by Wilcoxon test and Paired sample t-test was used to analyze anxiety variables.Results: Before the SSBM, all the elderly (100 percent) had poor sleep quality and the majority (93,3 percent) had moderate anxiety levels. Whereas after the intervention, the majority (93,3 percent) had good sleep quality and mild anxiety levels (73,3 percent). The p-value of the Wilcoxon test was 0,001 for sleep quality, and the p-value of paired sample t-test was 0,000 for anxiety.Conclusion: This study indicated that there was a positive effect of SSBM on sleep quality and anxiety levels in the elderly. It is recommended for nurses to widely implement SSBM to help reduce the elderly’s anxiety and sleep problems.